Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1529-8019.2010.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

Discoid chronic lupus erythematosus at the site of a previously healed cutaneous leishmaniasis: an example of isotopic response

Abstract: The term "isotopic response" describes the occurrence of a new skin disorder at the site of another, unrelated and already healed one. We report here the case of a 38-year-old woman who referred to us for an infiltrated, red-brownish plaque localized on her left cheek. The patient had been treated for a cutaneous leishmaniasis, confirmed by the histologic examination, localized at the same site. She was completely healed after an appropriate local and systemic treatment. She experienced the occurrence of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Theories underlying the pathogenesis behind Wolf’s isotopic response resembles much of the theory behind the Koebner phenomenon, with an inflammatory and autoimmune component resulting after a localized cutaneous trauma, although with the isotopic response, there may also be a neural, vascular, and viral component that explains its association with the herpes infection (19). Although cutaneous lupus has not been reported to have exhibited Wolf’s response after a herpes zoster infection, there has been report of a isotopic reaction with discoid chronic lupus erythematosus at the site of a previously healed cutaneous leishmaniasis lesion (20). Our patient had a preceding diagnosis of SLE with subsequent eruption of a new cutaneous lupus rash within the site of her prior herpes zoster lesion, making her presentation more consistent with the Koebner isomorphic response, although one could argue that our patient’s findings can be classified as an isotopic and an isomorphic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Theories underlying the pathogenesis behind Wolf’s isotopic response resembles much of the theory behind the Koebner phenomenon, with an inflammatory and autoimmune component resulting after a localized cutaneous trauma, although with the isotopic response, there may also be a neural, vascular, and viral component that explains its association with the herpes infection (19). Although cutaneous lupus has not been reported to have exhibited Wolf’s response after a herpes zoster infection, there has been report of a isotopic reaction with discoid chronic lupus erythematosus at the site of a previously healed cutaneous leishmaniasis lesion (20). Our patient had a preceding diagnosis of SLE with subsequent eruption of a new cutaneous lupus rash within the site of her prior herpes zoster lesion, making her presentation more consistent with the Koebner isomorphic response, although one could argue that our patient’s findings can be classified as an isotopic and an isomorphic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although these patients differed from each another in clinical and pathological diagnoses, obvious epidermal changes, such as hyperkeratosis, follicular plug, atrophy of stratum spinosum, or psoriatic hyperplasia showed that epidermal and follicular changes are common in WIR skin. In addition to the diseases mentioned above with skin and hair follicle changes, there have been diseases reported in the literature with the above manifestations, such as lupus erythematosus (23,24), granulomatous folliculitis (5,25), acquired perforating folliculitis (26), Trichophyton rubrum folliculitis (27), epidermal cyst (28), giant lichenification (29), poliosis (30), and molluscum contagiosum (31). As we noted above, we propose that the local network of nerve fibres is destroyed after VZV infection.…”
Section: Epidermal and Follicular Changes After Wolf's Isotopic Responsementioning
confidence: 66%
“…Cases of systemic lupus erythematosus and discoid lupus have been reported after herpes zoster infections in a dermatomal distribution 5, 6. Despite a 20-year history of systemic lupus, the only lupus-related skin findings that the patient experienced were nonphoto-exposed and within the dermatome previously affected by zoster.…”
Section: Discussionmentioning
confidence: 98%